Architecture: a capricchio, grouping famous houses of France.... - A. M. Perrot (Wellcome Collection)
Notice issue d Europeana. Lettering: Chateaux historiques de la France.
Droits : http://creativecommons.org/licenses/by/4.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie; Iconographie